2022
DOI: 10.3389/fmolb.2022.900533
|View full text |Cite
|
Sign up to set email alerts
|

How Do Pollen Allergens Sensitize?

Abstract: Plant pollen is one of the main sources of allergens causing allergic diseases such as allergic rhinitis and asthma. Several allergens in plant pollen are panallergens which are also present in other allergen sources. As a result, sensitized individuals may also experience food allergies. The mechanism of sensitization and development of allergic inflammation is a consequence of the interaction of allergens with a large number of molecular factors that often are acting in a complex with other compounds, for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 194 publications
0
10
0
Order By: Relevance
“…Homologues of Bet v 1 are panallergens involved in the development of pollen–pollen and pollen–food allergic cross-reactions due to their structural similarity and an ubiquitous presence in plant tissues [ 3 ]. It is well-known that the birch pollen allergen Bet v 1 is the main sensitizer of this class of allergens, causing cross-reactions in most cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homologues of Bet v 1 are panallergens involved in the development of pollen–pollen and pollen–food allergic cross-reactions due to their structural similarity and an ubiquitous presence in plant tissues [ 3 ]. It is well-known that the birch pollen allergen Bet v 1 is the main sensitizer of this class of allergens, causing cross-reactions in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Bet v 1-like proteins are generally heat sensitive, denature in an acidic environment, and, consequently, are rapidly degraded by gastric enzymes [ 11 ]. Therefore, food allergens of this class cause mostly mild allergic reactions—for example, oral allergic syndrome (OAS) [ 3 , 12 ]. At the same time, life threatening systemic allergic reactions, like urticaria and anaphylaxis, have also been described for some food homologues of Bet v 1, primarily, for the soybean Gly m 4 [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Der p 2, Bet v 1, or Fel d 1 belong to families of lipid‐binding proteins and Der p 2 mediates TLR4‐ but also TLR2‐dependent proinflammatory responses. The complexity of the allergen sensing serves as a reminder that our understanding of the innate immune programming of allergy and its interaction with genetic predispositions remains rudimentary 175–177 …”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the allergen sensing serves as a reminder that our understanding of the innate immune programming of allergy and its interaction with genetic predispositions remains rudimentary. [175][176][177] Despite all we have learned, our mechanistic understandings of how protease allergens induce the allergic response remains unresolved. Moreover, most of the data on protease allergens were focused on Der p 1 or proteolytically active HDM extracts, and it is presently unclear as to what extent these principles can be simply applied to other protease allergens.…”
Section: F I G U R Ementioning
confidence: 99%
“…Although pollen was considered a key allergen in AR and CSU, the intrinsic pathogenesis of how it leads to immune responses was still unclear. Studies have shown that Bet v1, one of the most significant plant allergens in pollen, can be recognized by T cells in individuals with birch pollen allergy ( 19 , 20 ). It was also widely accepted that immune responses to airborne allergens likely involve two subsets of CD4+ T cells, namely Tfh cells and Th2 cells ( 21 ).…”
Section: Introductionmentioning
confidence: 99%